Giving Effectiveness Against Decline Stew Ginger Nausea Vomiting In Pregnancy Trimester I, BPM Deliana. S 2016 - Novita Lusiana (Universitas Pahlawan Tuanku Tambusai, 2017)
Emesis Gravidarum is nausea and vomiting are common in the morning, but will disappear in a few hours that occur during trimester I. Nausea and vomiting is caused by increased estrogen, progesterone and human chorionic gonadotropin expenditure. In general, people reduce nausea and vomiting by taking anti-nausea medicine. The anti-nausea madicine that can be used by the public like ginger decoction and vitamin B6. Therefore, this study aimed to determine the effectiveness of ginger decoction to decrease nausea and vomiting in Deliana’s BPM. The research design was quasi experimental with pre-test and post-test in the experimental group and the control group. The population in this research that all pregnant women in the first trimester in Deliana’s BPM. , samples are 30 people in this research using observation sheet. The data analysis used paired test. Statistical test results showed that the average level of nausea and vomiting of pregnant women after drink of decoction ginger is 8.00. This value is higher than the value of the average rate of nausea and vomiting after given Vitamin B6 is 7.50. With a p-value of 0.000 <α (0.05), it can be concluded that there are significant differences ginger drink decoction to decrease nausea and vomiting in pregnant women in the first trimester in Deliana’s BPM. The conclusion from this research is that ginger is more effective in reducing nausea and vomiting in pregnant women in the first trimester BPM Deliana S 2016 is attested by the average difference between the reduction in nausea and vomiting by giving ginger higher than giving Vitamin B6